2010
DOI: 10.1016/j.ijporl.2010.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Clonal spread of β-lactamase-producing amoxicillin–clavulanate-resistant (BLPACR) strains of non-typeable Haemophilus influenzae among young children attending a day care in Japan

Abstract: Objective: Resistant strains of non-typeable Haemophilus influenzae (NTHi) are one of the principal causes of recurrent acute otitis media (otitis prone), rhinosinusitis, and pneumonia in young children. β-lactamase-nonproducing ampicillin-resistant (BLNAR) strains are particularly common in Japan, and β-lactamase-producing amoxicillin-clavulanate resistant (BLPACR) strains are now emerging. We investigated the nasopharyngeal carriage status of these resistant strains among children attending a same day care c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…The prevalence of H. influenzae was similar or lower than other colonization studies conducted on worldwide centers. 2,7,10,13,14,19,20 Recently, Carvalho et al 7 reported NTHi colonization in 32% of the children from DCCs in a large Brazilian city with a frequent antibiotic use (> 80%) within the studied population, 7 while studies in the United States showed a carriage rate of 64%. 2,10 Antimicrobial susceptibility was high probably due to the low range of antimicrobial agents given to treat infections in children.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The prevalence of H. influenzae was similar or lower than other colonization studies conducted on worldwide centers. 2,7,10,13,14,19,20 Recently, Carvalho et al 7 reported NTHi colonization in 32% of the children from DCCs in a large Brazilian city with a frequent antibiotic use (> 80%) within the studied population, 7 while studies in the United States showed a carriage rate of 64%. 2,10 Antimicrobial susceptibility was high probably due to the low range of antimicrobial agents given to treat infections in children.…”
Section: Discussionmentioning
confidence: 98%
“…16 Although NTHi is considered less virulent than Hib, it can be responsible for severe diseases, especially among children with previous comorbidities. 11 Several studies have been performed to establish the H. influenzae carriage rate after vaccine introduction, 2,7,10,[12][13][14][19][20][21] although to our knowledge, no studies have been reported from Spain. Longitudinal studies performed on one or two selected DCCs give information about the dynamics of colonization, but fail to give an overall view of the situation in similar centers of the same geographical area.…”
Section: Discussionmentioning
confidence: 99%
“…Otitis media is the most common reason for children in industrialized countries to receive antimicrobial therapy, and children play an important role in transmission of resistant isolates into the community (40). Infections in COPD are one of the most common indications for antimicrobial therapy in adults.…”
Section: Vaccines To Reduce Antimicrobial Resistancementioning
confidence: 99%
“…Sin embargo, en los últimos años, desde la introducción de las vacunas antineumocócicas conjugadas, H. influenzae no tipificable productor de betalactamasas tiene cada vez más relevancia, sobre todo en las OMA recurrentes o persistentes 43 . Además, se calcula que una de cada 8 o 9 otitis producidas por esta bacteria no responde a la amoxicilina 44,45 .…”
Section: Elección Del Antibióticounclassified